Atopic triad (allergic rhinitis, eczema, and asthma) and eye rubbing as risk factors for keratoconus: a systematic review and meta-analysis - Albalawi, Abdulmajeed; Alharbi, Alanoud; Alhasani, Hussain; Alharbi, Amal; Abdullah, Raghad; Alamrani, Abrar; Althobaiti, Amal; Albalwi, Ziad; Alblowi, Yassmeen; Albalawi, Nuwayr; Albalawi, Nujud; Alhwaiti, Atheer; et al. (International Journal Of Community Medicine And Public Health, 2021)
Keratoconus (KN), is an eye disorder, characterized by progressive thinning and protrusion of central cornea. A number of conditions such as such as allergy, asthma, eczema, and eye rubbing has been shown to be associated with the development of KN. However, there is a disagreement regarding some of risk factors and their strength so we conducted systematic review and meta-analysis to determine how strongly risk factors such as eye rubbing, and atopic triad associate with KN development and progression. We systematically searched the literature for related studies using specific keywords and key phrases. The studies were scrutinized based on inclusion and exclusion criteria. Finally, we extracted relevant qualitative and quantitate information from studies. For meta-analysis we used odds ratio (OR) and their 95% CI were used to draw forest plots. 35 studies were selected in final meta-analysis. Our meta-analysis yielded the combined effect of risk factors with OR of 2.20 and a 95% CI of 1.84–2.64. Furthermore, we found that eye rubbing-related studies had effect size of OR 2.09 with a 95% CI of 1.76–2.49 and a p value of 0.00001. For atopic triad (allergic rhinits, asthma and eczema) related studies, the meta-analysis yielded overall effect size of OR 2.34 with 95% CI of 2.06-2.66. Eye rubbing and atopic triad (allergic rhinitis, eczema, and asthma) are important risk factors for KC development with statistically strong association.